Faktor-Faktor yang Berhubungan dengan Fraud Pengadaan Barang/Jasa di Lembaga Publik - Nashirotun Nisa Nurharjanti (Journal of Accounting and Investment, 2017)
The purpose of this study was to test whether the variable quality of the procurement committee of goods/services, quality of the patners goods/ services, systems and procedures for procurement of goods/services, ethical procurement of goods/services, environmental goods/services, and risk assessment have an influence on the procurement fraud goods/services in University. This study using survey method by distributing questionnaires in Asset Management and Maintenance Directorate of the University with the involvement of officials making commitments (PPK) totaling 3, the committee procurement of goods/services amounted to 22 people, and committee work proceeds amounted to 25 examiners. The gathered data was analyzed using multiple regressions in SPSS software. The result showed that the quality of procurement commite, supplier’s quality, procurement system and procedure, and risk assesment had negatively influenced toward fraud in the procurement goods/services.  Meanwhile, the procurement ethics and frameworks did not have influenced toward fraud in the procurement goods/services